Recurrent Mitral Regurgitation After MitraClip: Predictive Factors, Morphology, and Clinical Implication. (March 2022) - Sugiura, Atsushi; Kavsur, Refik; Spieker, Maximilian; Iliadis, Christos; Goto, Tadahiro; Öztürk, Can; Weber, Marcel; Tabata, Noriaki; Zimmer, Sebastian; Sinning, Jan-Malte; Mauri, Victor; Horn, Patrick; et al.
Abstract : Background: Recurrent mitral regurgitation (MR) following MitraClip has not been thoroughly investigated. We aimed to examine the predictive factors, morphology, and long-term outcome of recurrent MR after MitraClip. Methods: We assessed data from the Heart Failure Network Rhineland registry from August 2010 to October 2018. Competing risk analyses were performed using the Fine and Gray model to assess the risk of recurrent MR. Results: Among 685 MitraClip patients with a reduction in MR to ⩽2+, 61 patients developed recurrent MR within the first 12 months. Flail leaflet (hazard ratio, 3.68; P =0.002) and residual MR (MR grade 2+ versus ⩽1+: hazard ratio, 2.56; P =0.03) were the predictors of recurrent MR in primary MR patients, while left atrial volume (per 10 mL increase: hazard ratio, 1.11; P <0.001) and residual MR (hazard ratio, 2.45; P =0.01) were independently associated with recurrent MR in secondary MR patients. In primary MR patients, loss of leaflet insertion or leaflet tear were the predominant morphologies with recurrent MR. In secondary MR patients, more than half of the patients with recurrent MR did not show any disorder of the clip or leaflets. Patients with recurrent MR were more likely to experience unplanned heart failure hospitalization or heart failure symptom with New York Heart Association scale III/IV (54.1% versus 37.8%; P =0.018) and undergo a repeat mitral valve intervention (9.8% versus 2.2%; P =0.005) during the follow-up. In the landmark survival analysis, patients with recurrent MR tended to have lower long-term survival (58.7% versus 83.9%; P =0.08) than patients without recurrent MR. Conclusions: Flail leaflet and residual MR were the predictors of recurrent MR in primary MR patients, while a larger left atrial volume and residual MR were associated with recurrent MR in secondary MR patients, which may be associated with long-term clinical outcomes of patients after MitraClip.